Floatinghearts: Nymphoides spp. - Ian J. Markovich; Joseph W. Sigmon; Lyn A. Gettys (EDIS)
The purpose of this publication is to teach interested readers how to identify and distinguish among species of floatinghearts in Florida. Written by Ian J. Markovich, Joseph W. Sigmon, and Lyn A. Gettys, and published by the UF/IFAS Agronomy Department, October 2022.